Managing Capital Flows: The Case of the Philippines - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2008)
During the past five years or so, most East Asian economies including the Philippines experienced a rising level of foreign exchange reserves and rapidly appreciating currencies both in nominal and real terms. One cause has been the resurgence of capital flows, which makes the issue of how to manage them relevant. However, the experience with regard to capital flows among East Asian economies is mixed and the level of capital flows to the region is proportionally less than that prior to the 1997 crisis. Another reason is the rise in current account surpluses. The Philippines has experienced both a return of capital inflows and a more favorable current account balance, with the latter largely due to remittances from overseas workers. However, like many other regional currencies, the appreciation of the peso is not commensurate to movements of the BOP accounts. Currencies in the region are reacting primarily to the general weakness of the US dollar, and global uncertainties have contributed to weak investment which in turn is another major reason behind the current account surplus of several economies including the Philippines. Policy measures at the domestic level can focus on reviving private investment, particularly channeling overseas remittances to more productive investment. Meanwhile, East Asian financial and monetary cooperation can also result in a unified front aimed at overhauling the unipolar global financial system.
Keywords: 330; foreign exchange inflows; currency appreciation; unipolar global financial system; Kapitalmobilität; Kapitalimport; Kapitalverkehrskontrolle; Schätzung; Philippinen